Effect of Schiff base combination on liver cancer - Dogan, A.; Basak, N.; Telci, D.; Dede, B.; Kilic, E.; Kilic, K.; Sahin, F. (Wiley-Blackwell, 2013)
[Abstract Not Available]
38th Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUL 06-11, 2013 -- Saint Petersburg, RUSSIA